Peran Guru dalam Pembelajaran: Strategi Menanamkan Pendidikan Karakter di Era Pandemi Covid-19 - Rahmat Catur Abdian; Suryo Ediyono (Universitas Sebelas Maret, 2022)
Character education is an effort to instill character values which include knowledge, awareness or will, and action. Character education aims to shape the mindset, attitudes, and behavior of students to become individuals with noble character, both in relation to God Almighty, oneself, the community, as well as the nation and state. The current situation of the covid-19 pandemic is a problem for the world of education, especially formal education in an effort to instill character education. Learning is currently mostly carried out online, so it becomes a challenge for teachers in the process of instilling character education. This study aims to describe the role of teachers in instilling character education in the era of the covid-19 pandemic. In this study, the author uses the library study method by collecting several articles and other written sources that are in accordance with the theme of the discussion. The results of the study show that the synergy between teachers, parents, and the community is very much needed to realize the behavior of students with character in the midst of the covid-19 pandemic.